2004
DOI: 10.1128/jvi.78.7.3722-3732.2004
|View full text |Cite
|
Sign up to set email alerts
|

Positive Selection Detection in 40,000 HumanImmunodeficiency Virus (HIV) Type 1 Sequences Automatically IdentifiesDrug Resistance and Positive Fitness Mutations in HIV Proteaseand ReverseTranscriptase

Abstract: Drug resistance is a major problem in the treatment of AIDS, due to the very high mutation rate of human immunodeficiency virus (HIV) and subsequent rapid development of resistance to new drugs. Identification of mutations associated with drug resistance is critical for both individualized treatment selection and new drug design. We have performed an automated mutation analysis of HIV Type 1 (HIV-1) protease and reverse transcriptase (RT) from approximately 40,000 AIDS patient plasma samples sequenced by Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 25 publications
5
109
0
1
Order By: Relevance
“…The first indication of this novel secondary structure came from our previous studies of HIV mutation covariance in clinical HIV samples (Chen et al 2004;Wang and Lee 2007), which identified the unusual pattern of synonymous mutation covariance shown in Figure 4. The clear ''diagonal'' pattern in the covariance matrix, the remarkable conservation of Watson-Crick base-pairing by compensatory mutations, and the obvious sequence complementarity of these regions immediately indicated an RNA secondary structure.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The first indication of this novel secondary structure came from our previous studies of HIV mutation covariance in clinical HIV samples (Chen et al 2004;Wang and Lee 2007), which identified the unusual pattern of synonymous mutation covariance shown in Figure 4. The clear ''diagonal'' pattern in the covariance matrix, the remarkable conservation of Watson-Crick base-pairing by compensatory mutations, and the obvious sequence complementarity of these regions immediately indicated an RNA secondary structure.…”
Section: Discussionmentioning
confidence: 91%
“…We computed a measure of synonymous variability from a data set of about 20,000 HIV-1 subtype B sequences (Chen et al 2004). Following the previous analysis of Gog et al (2007), synonymous variability was calculated for each codon position as the normalized mean pairwise distance (MPD) (raw data shown in Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations